2021
DOI: 10.1007/s11102-021-01195-8
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism chemical prophylaxis after endoscopic trans-sphenoidal pituitary surgery

Abstract: Purpose There is no compelling outcome data or clear guidance surrounding postoperative venous thromboembolism (VTE) prophylaxis using low molecular weight heparin (chemoprophylaxis) in patients undergoing pituitary surgery. Here we describe our experience of early chemoprophylaxis (post-operative day 1) following trans-sphenoidal pituitary surgery. Methods Single-centre review of a prospective surgical database and VTE records. Adults undergoing first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…44 Therefore, giving thromboprophylaxis during active disease and/or post-operatively remains an individual decision and should be taken into account. According to a study by Waqar et al 47 , chemoprophylaxis with tinzaparin reduced the risk for post-operative VTEs without an increased risk for significant bleeding events.…”
Section: Thromboembolismmentioning
confidence: 99%
“…44 Therefore, giving thromboprophylaxis during active disease and/or post-operatively remains an individual decision and should be taken into account. According to a study by Waqar et al 47 , chemoprophylaxis with tinzaparin reduced the risk for post-operative VTEs without an increased risk for significant bleeding events.…”
Section: Thromboembolismmentioning
confidence: 99%
“…A specific thromboprophylaxis protocol for patients with CS was not available in the vast majority of centers, despite the fact that retrospective cohort studies have shown a decrease in VTE-associated mortality and morbidity in patients with endogenous hypercortisolism on anticoagulant treatment ( 20 , 21 ). Thromboprophylaxis in CS patients has been reported to be associated with low bleeding rates ( 22 , 23 ), which is confirmed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…10,11 Based on the elevated VTE risk after TSS for CD, it appears that chemoprophylaxis postoperatively in addition to me-chanical prophylaxis is warranted. 3,10,11,20 Based on prior data, it appears that starting subcutaneous heparin within 24 hours postoperatively carries low risk of sellar hematoma or epistaxis. However, the total duration of chemoprophylaxis (e.g., in-hospital only, 7, 14, or 28 days) remains uncertain.…”
Section: Discussionmentioning
confidence: 99%